Neutrino mass ordering determination through combined analysis with JUNO and KM3NeT/ORCA. (24th November 2021) - Chau, N.; Athayde Marcondes de André, J.P.; Van Elewyck, V.; Kouchner, A.; Kalousis, L.; Dracos, M.
Abstract: The neutrino mass ordering (NMO) is one of the fundamental questions in neutrino physics. KM3NeT/ORCA and JUNO are two neutrino oscillation experiments both aiming at measuring the NMO with different approaches: ORCA with atmospheric neutrinos traversing the Earth and JUNO with reactor neutrinos. This contribution presents the potential of determining the NMO through a combined analysis of JUNO and ORCA data. In a joint fit, the NMO sensitivity is enhanced beyond the simple sum of the sensitivities of each experiment due to the tension between the respective Δ m 31 2 best fit values obtained when the wrong ordering is assumed, together with good constraints on this parameter measurement by both experiments. From this analysis, we expect the true NMO to be determined with 5 σ significance after 1–2 years of data taking by both experiments for the current global best-fit values of the oscillation parameters, while maximally 6 years will be needed for any other parameter set.